Cosmetic company commitment to the international organization for standardization (ISO) as a private authority regime - Nazlatunnuha, Dinda Fitri (Jurnal Inovasi Ilmu Sosial dan Politik (JISoP), 2023)
This research discusses the ISO private authority regime with a focus on the ISO 14001 series issues regarding the environmental management system at the cosmetics company The Body Shop. The aim of this research is to determine the commitment of The Body Shop through policies as a form of company compliance with the international private regime and its contribution achievements. This research analysis uses concepts International Private Regime and Institutional Theory with descriptive methods of qualitative data analysis collected through documentation study techniques. The results of this research found that the ISO 14001 standard is an international private regime that regulates management systems environment is not a standard of technical performance in companies. In this way, The Body Shop's commitment to ISO 14001 is proven through the existence of a circular economy policy, reducing greenhouse gas emissions towards net zero carbon, to policies related to company design and product raw materials used in order to minimize environmental impacts. This shows that The Body Shop has a high commitment to implementing ISO 14001 standards in its business activities green corporate.